https://dergipark.org.tr/tr/download/article-file/3787835 - Burcu Küçükkaya; Mehtap Temiz (Ahi Evran Medical Journal)
The Enhanced Recovery After Surgery (ERAS) protocol refers to multifaceted evidence-based interventions applied to reduce the duration of hospital stay and the risk of complications for patients after the surgical procedure. In this context, it is effective in different types of major surgery, including surgery of gynecological cancers. Especially since the Hyperthermic Intraperitoneal Chemotherapy After Cytoreductive Surgery (SRCHIPEK) procedure is a major and complex procedure with high complication, morbidity and mortality rates, preparation and care in the preoperative period are of great importance. For patients planned for SRCHIPEC, gynecology nurses have responsibilities such as informing and counseling the patient with the ERAS protocol approach within the scope of evidence-based practices, teaching healthy lifestyle behaviors, evaluating nutrition and anemia status, ensuring immunonutrition, assessing cardiac risk and function, and avoiding unnecessary premedication, monitoring sedative/anxiolytic use and side effects, preventing long-term fasting before the procedure with planned preoperative preparations, maintaining and frequent monitoring of normothermia and normoglycemia. Thus, the incidence of complications in women with ovarian cancer who have undergone SRCHIPEC will decrease, patients will be able to meet their basic needs independently, they will be able to be discharged earlier, and therefore they will be able to return to social life more quickly. The aim of this review is to examine the evidence-based practices used in the preoperative management of the hyperthermic intraperitoneal chemotherapy procedure after cytoreductive surgery, which is planned to be applied to patients with ovarian cancer, and the roles and responsibilities of nurses in the ERAS protocol.